Turkish Cross-Cultural Adaptation of the BRIEF-MPI in Older Adults with Cancer: Convergent and Discriminative Validity Compared with the G8 and Clinical Frailty Scale - Sercan On; Haydar Cagatay Yuksel; Semih Sergen Semerci; Ecem Ozdemir; Mustafa Kagan Ozdel; Fatma Ozge Kayhan Kocak (Healthcare, 2026)
Background: Older adults with cancer represent a heterogeneous population with varying levels of frailty and multidimensional vulnerability. Rapid screening tools are needed to identify patients who may benefit from comprehensive geriatric assessment (CGA). This study aimed to translate and culturally adapt the Brief Multidimensional Prognostic Index (BRIEF-MPI) into Turkish and evaluate its performance in older adults with cancer. Methods: This cross-sectional methodological study included 177 patients aged ≥65 years with solid malignancies. The BRIEF-MPI was translated and culturally adapted using a structured cross-cultural adaptation process. Clinical performance was evaluated by comparison with the G8 screening tool and the Clinical Frailty Scale (CFS). Correlations with frailty-related measures were assessed using Spearman’s rank correlation. Receiver operating characteristic (ROC) analyses were performed to evaluate discriminative performance for identifying CFS-defined frailty. Results: The mean age was 72.5 ± 5.8 years, and 56.5% of participants were women. A positive BRIEF-MPI screening (classes 2–3) was identified in 17.5% of participants, whereas 50.8% screened positive according to the G8. Both instruments were significantly associated with CFS-defined frailty (p